The shear stress properties of ester lubricants in elastohydrodynamic contacts - Chang,H; Spikes,HA; Bunemann,TF (Journal of Synthetic Lubrication, 1992)
Abstract This paper describes a systematic study into the influence of molecular structure on lubricant shear stress in elastohydrodynamic (EHD) contacts. An infrared emission technique has been employed to measure surface temperatures in an EHD contact and thence to determine the shear stress profile of lubricant films therein. The effect of structure on shear stress has been investigated by comparing the behaviour of a range of wellcharacterised, closely related, ester base fluids. Considerable variations in shear stress response to EHD conditions have been observed, depending upon the type and structure of the ester.